THE VALUE OF ABS-SBK IN TENGGELAMNYA KAPAL VAN DER WIJCK BY HAMKA - Harris Effendi Thahar (Fakultas Bahasa dan Seni UNP, 2016)
The Tenggelamnya Kapal Van der Wijck is a phenomenal Hamka’s novel. One of the most important values in this novel is the author's criticism of the implementation of Minangkabau adat (custom) claiming to be based on the Islamic religion contained in the adatum Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS-SBK) ‘custom is based on syariah, syariah is based on the Kitabullah (Al Quran)’. While in